The Effect Of Bracket Ligation Method On Canine Retraction - Alhuwaizi , Akram F; Jasim , Esraa J (Journal of Baghdad College of Dentistry, 2017)
Aim: This study aimed to compare different types of ligation methods to obtain maximum tooth movement with the least undesirable rotation. Methods: Titanium brackets bonded to acrylic canine teeth were ligated to straight stainless steel (SS) archwires using four ligation methods (figure-O and figure-8 elastics, SS ligatures, and Leone Slide ligatures). The teeth with the ligatures in place were stored in a water bath at 37ÂºC for 1 day, 1 week, 2, 4 or 6 weeks before testing. The teeth were retracted through softened wax along the archwire and the amount of tooth movement and degree of rotation were measured. Results: Slide ligatures showed the highest distance of tooth movement and degree of canine rotation followed by figure-O elastics, while figure-8 elastics showed the least amount of retraction and degree of rotation. SS ligatures showed moderate tooth movement with a minimal degree of rotation. Conclusions: The study recommends the use of loose SS ligatures for canine retraction in sliding mechanics, while Slide elastic ligatures are best used in leveling and aligning stage of crowded teeth since they showed reduced friction with the archwire.